Respuesta :
f(x)=(x-8)(x+3)
f(x)=x^2 - 8x + 3x - 24
y-intercept when x = 0 so then f(x) = -24
answer
y-intercept (0, -24)
f(x)=x^2 - 8x + 3x - 24
y-intercept when x = 0 so then f(x) = -24
answer
y-intercept (0, -24)
The curve passes through y-axis at [tex]x=0[/tex]
Substituting [tex]x=0[/tex] into [tex]f(x) = (x-8)(x+3)[/tex] we have:
[tex]f(0) = (0-8)(0+3)[/tex]
[tex]f(0)=(-8)(3)[/tex]
[tex]f(0)=-24[/tex]
The y-intercept is -24
Substituting [tex]x=0[/tex] into [tex]f(x) = (x-8)(x+3)[/tex] we have:
[tex]f(0) = (0-8)(0+3)[/tex]
[tex]f(0)=(-8)(3)[/tex]
[tex]f(0)=-24[/tex]
The y-intercept is -24